Targeting multiple water utilities using composite curves - Alwi, Sharifah Rafidah W.; Manan, Zainuddin A. (American Chemical Society, 2007)
The majority of techniques to determine the minimum water targets based on water pinch analysis (WPA) have assumed freshwater as the sole utility that exists at zero concentration. In practice, regenerated water and externally outsourced water such as rainwater, river water, snow, and imported spent water may exist at varieties of concentrations and can be used to reduce freshwater utility. This paper presents new procedures to establish the minimum flow rate targets for multiple water utilities using the source and sink composite curves. The work offers significant new insights into systematic placement of multiple new utilities through water outsourcing in the context of WPA